Cycling has made a comeback: has it returned to Brussels as well? - Amandine Henry; Thomas Ermans; Fanny de Smet d’Olbecke (Brussels Studies, 2020)
In recent years, cyclists seem to be taking over the streets of the capital. Does this increased visibility really reflect a return of cycling in Brussels? How can we obtain an accurate understanding of the evolution of cycling? In this fact sheet, the authors explore the different sources and approaches which make it possible to quantify cycling in Brussels. They make use of the various inputs to describe the major trends in its recent evolution.